Development and pathogenicity of lung fluke, Paragonimus westermani, in experimental animals - Tu, Luu Anh; Doanh, Pham Ngoc; Hien, Hoang Van (Academia Journal of Biology, 2016)
Lung fluke, P. westermani, has wide distribution in Asia and has been identified as the most important pathogen for human paragonimiasis. The definitive hosts, including humans, become infected through eating crabs containing metacercariae or paratenic hosts harboring juveline worms. In Vietnam, metacercariae of P. westermani have been detected in central provinces at high infection prevalence. In this study, we determined the development and pathogenicity of P. westermani in experimental animals. The results of experimental infections showed that Vietnamese P. westermani population does not develop in domestic dogs, but can grow to adults in domestic cats at low developmental rates and require relatively long time to maturity. The worms lived in extrapulmonary or live in pairs to form cysts in the lungs. Most of them are immature. In mice, juveline worms were collected in the muscles and livers. The flukes were morphologically similar to the excysted metacercariae except for their slightly larger body size. These juveline worms can grow to adults in cats when they were orally given to cats, confirming the role of paratenic hosts in life cycle of P. westermani in Vietnam. This study suggests that wild animals can serve as paratenic hosts and definitive hosts of P. westermani. Protection of wildlife should pay attention to paragonimiasis, and not eating undercooked crabs as well as meat of other animals to avoid Paragonimus infection.